2021
DOI: 10.21203/rs.3.rs-378436/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Distant Metastatic Recurrence By Tumor-Infiltrating Lymphocytes in Hormone Receptor-Positive Breast Cancer

Abstract: Background: Breast cancer subtypes are known to have different metastatic recurrence sites. Distant metastases are often observed during the post-operative course in patients with human epidermal growth factor receptor 2 (HER2)-enriched breast cancer and triple-negative breast cancer, but are relatively rare in those with hormone receptor-positive and HER2-negative (HR+/HER2-) breast cancer. Tumor-infiltrating lymphocytes (TILs) serve as an index to monitor tumor immune microenvironment and may possibly predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We further explored the correlations between the clinical response and baseline immune-related biomarkers in this clinical trial. It has been reported that the levels of patient serum cytokines, tumor mutation burden and immune checkpoints as well as the infiltrated immune cell composition may affect and predict the clinical achievement of TIL-based ACT treatment (46)(47)(48)(49)(50)(51). Here, we observed that low levels of immune inhibitory factors, such as TOX and Foxp3, and high infiltrated lymphocyte numbers in tumor tissues, as well as high baseline levels of inflammatory cytokines, may predict a clinical benefit for auto-TIL treatment.…”
Section: Discussionmentioning
confidence: 51%
“…We further explored the correlations between the clinical response and baseline immune-related biomarkers in this clinical trial. It has been reported that the levels of patient serum cytokines, tumor mutation burden and immune checkpoints as well as the infiltrated immune cell composition may affect and predict the clinical achievement of TIL-based ACT treatment (46)(47)(48)(49)(50)(51). Here, we observed that low levels of immune inhibitory factors, such as TOX and Foxp3, and high infiltrated lymphocyte numbers in tumor tissues, as well as high baseline levels of inflammatory cytokines, may predict a clinical benefit for auto-TIL treatment.…”
Section: Discussionmentioning
confidence: 51%